Sacroiliac Joint Index in Healthy Pakistani Population and Patients with Sacroiliitis Using Technetium-99m Methylene Diphosphonate Bone Scintigraphy - Ibrahim, Muhammad Usman; Hussain, Fida; Adil, Muhammad; Ibrahim, Muhammad Imran; Dar, Zaigham `Salim; Sikandar, Zeeshan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the values of the Sacroiliac Joint Index (SI Index) in normal population and patients with sacroiliitis (SI) and the correlation of normal values with age and gender. Study Design: Prospective longitudinal study. Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Dec 2020 to Jul 2022. Methodology: A total of 140 patients (Group-I consisting of 129 cancer patients having no clinical or radiological evidence of SI referred for metastatic/staging workup and Group-II consisting of 11 patients with clinical, laboratory and radiological diagnosis of ankylosing spondylitis) who underwent whole body bone scintigraphy using Technetium Pertechnetate (Tc-99m) labelled Methylene Diphosphonate (MDP) were included. The SI Index was calculated for each patient using the sacroiliac joint (SIJ) to sacrum radiotracer uptake ratio using the ROI method. Results: The mean SI Index was 1.02±0.09, (range: 0.87-1.24) in normal individuals while 1.28±0.09 (range: 1.15-1.53) in patients with SI. A significant statistical difference was observed in both groups for the SI Index (p-<0.001). In addition, the SI Index was significantly associated with age (p=0.016) in the normal population. Conclusion: The SI Index quantification using bone scintigraphy is a sensitive and cost-effective method for detecting SI. In addition, the SI Index differs according to age, so a different cut-off value should be used for each group.